Exploring the Impact of Lived Experience Contributions to Social Work and Healthcare Programmes: A Scoping Review - Rathna Bharathi Seetharaman; Joanna Fox; Gavin Millar (Social Sciences, 2025)
The integration of lived experience educators (LEEs) in social work and healthcare educational programmes has evolved to recognise its potential to enhance learning, empathy and professional development among students. This scoping review explores the level of LEEs’ engagement in academic models and the different perspectives of LEEs, academic staff and students on lived experience education, analysing both the merits and challenges of this pedagogical approach. A systematic search was conducted across multiple academic databases and identified 37 articles on lived experience education. Arnstein’s Ladder of Citizen Participation was used as an evaluation tool to assess the levels of engagement described in the studies. The common themes across studies were analysed and synthesised for each perspective of the stakeholders. The findings of this review evidence that while lived-experience-led education enhances students’ performance, the depth of participation of LEEs varies widely. The ladder-level analysis found that many educational programmes are designed at the higher rungs of “co-production”, where LEEs collaborate equally with academics. However, some practices are at the lower rungs of “tokenism”, where LEEs are consulted but have limited decision-making power. This may be due to challenges such as a lack of structured support systems, emotional labour for LEEs and inconsistencies in practice. Therefore, greater efforts are needed to move beyond tokenistic involvement towards meaningful co-production in education for people-centred services. By embedding lived experience contributions, education becomes a synergistic practice, continuously shaping and enriching the professional development of both students and the communities they serve.